Expression, purification and crystallization of a fungal type III polyketide synthase that produces the csypyrones. Issue 6 (1st June 2014) - Yang, Dengfeng; Mori, Takahiro; Matsui, Takashi; Hashimoto, Makoto; Morita, Hiroyuki; Fujii, Isao; Abe, Ikuro
<x xml:space="preserve">Abstract</x> CsyB from Aspergillus oryzae is a novel type III polyketide synthase that catalyzes the formation of csypyrone B1 [4‐(3‐acetyl‐4‐hydroxy‐2‐oxo‐2H‐pyran‐6‐yl)butyric acid] from fatty acyl‐CoA, malonyl‐CoA and acetoacetyl‐CoA. Recombinant CsyB expressed in Escherichia coli was crystallized by the sitting‐drop vapour‐diffusion method. The crystals belonged to space P21, with unit‐cell parameters a = 70.0, b = 104.8, c = 73.5 Å, β = 114.4°.